Market-Driving Behavior in Emerging Firms A Study on Market-Driving Behavior, its Moderators and Performance Implications in German Emerging Technology Ventures - Neuenburg, Jesko-Philipp.; SpringerLink (Online service) (Wiesbaden : Gabler Verlag : Imprint: Gabler Verlag, 2010)
Market orientation has been established as a source of company success over the past 20 years. Jesko-Philipp Neuenburg researches the market-driving behavior – i.e. the behavior of a company that is directed to fundamentally change the structure of the market and/or behavior of market stakeholders – in emerging firms on a theoretical as well as an empirical level. A study of 224 emerging technology firms in Germany is presented and the results indicate that market-driving behavior has a positive influence on firm success.
Basics of investigation -- Conceptualization of market-driving behavior in emerging firms -- Measurement of market-driving behavior in emerging firms -- Empirical study of market-driving behavior in emerging technology firms -- Discussion -- Summary.
Keywords: Marketing; Management; Marketing; Management